Colonic Microbiota and Metabolites Response to Different Dietary Protein Sources in a Piglet Model - Li, Rui; Chang, Ling; Hou, Gaifeng; Song, Zehe; Fan, Zhiyong; He, Xi; Hou, De-Xing (Frontiers in Nutrition, 2019)
Dietary protein sources have the potential to affect the colon microbiome of piglets that will subsequently have a large impact on metabolic capabilities and hindgut health. This study explored the effects of different protein sources on the growth performance, diarrhea rate, apparent ileal digestibility (AID) of crude protein (CP), colonic mucin chemotypes, colonic microbiome, and microbial metabolites of piglets. Twenty-four piglets were randomly divided into four groups that received isoenergetic and isonitrogenous diets containing either Palbio 50 RD (P50), Soyppt-50% (S50), concentrated degossypolized cottonseed protein (CDCP), or fish meal (FM) as the sole protein source. The experimental diets did not affect the estimated daily gain (EDG), but P50 increased fecal score compared with S50 and CDCP. CDCP increased, but P50 reduced AID of CP in comparison to FM and S50. S50 and CDCP increased the amount of mixed neutral-acidic mucins relative to P50. Venn analysis identified unique OTUs in the P50 (13), CDCP (74), FM (39), and S50 (31) groups. The protein sources did not change the colonic bacterial richness or diversity. High Escherichia abundance in the P50 and FM, great abundant of Lactobacillus in the CDCP, and high Gemmiger abundance in the S50 were found. The CDCP tended to elevate valeric acid and branched chain fatty acid (BCFA) concentrations compared with the other diets. The P50 and FM groups had greater ammonia nitrogen and methylamine contents than the S50 and CDCP groups. There was a positive correlation between the Escherichia and ammonia nitrogen, the Lactobacillus and short chain fatty acid (SCFA), and a negative correlation between the Gemmige and BCFA. These findings suggested short-term feeding of different protein sources did not affect the piglets' growth, but P50 increased the diarrhea rate. Potential pathogenic bacteria and detrimental metabolites appeared in the colons of piglets fed P50 and FM, whereas, beneficial effects were conferred upon piglets fed CDCP and S50, thus indicating that available plant proteins (cotton seed, soy) added to the diets of piglets enhanced colon health by reducing protein fermentation.